Strategy Analysis of KOTAKU (Slum-Free City) Program on Housing and Environmental Problems in Kudus Regency - Saefudin, Achmad; Rahmawati, Rukhaini Fitri; Muharram, R. Hefi Achid (IJTIMAIYA: Journal of Social Science and Teaching, 2024)
This research analyzes the problem of slum settlements in Indonesia, focusing on Kudus Regency. The main issues identified include rapid population growth, limited land, and lack of basic infrastructure. The method used is secondary data analysis from various official sources and literature studies. The research results show that around 15% of residential areas in Kudus are categorized as slums, with the main problems including poor sanitation, inadequate drainage, and building density. This research concludes that an integrated approach involving collaboration between the government, the private sector, and the community is needed to develop innovative and sustainable solutions to overcome the problem of slum settlements in Kudus Regency.